Eksplorasi Perkembangan Emosional Anak Pra-Sekolah dalam Lingkungan Keluarga dengan Pola Asuh Demokratis - Aulia Nuurin Mahfudloh (STIKes Ibnu Sina Ajibarang, 2025)
This research explores the emotional development of preschool children in a family environment with democratic parenting through a systematic analysis of the literature. Preschool-aged children are in a critical period of emotional development, where the role of parents and the parenting styles implemented have a significant influence on their emotional growth. This research examines various studies that focus on the impact of democratic parenting on the emotional development of preschool children. The results show that democratic parenting contributes positively to children's emotional development, helping them develop independence, self-confidence and the ability to solve problems. The method used in this research is Systematic Literature Review (SLR), which includes identification, evaluation, and interpretation of relevant research. The studies analyzed show consistency in the findings that democratic parenting supports optimal emotional development in preschool children.